Proceedings of the 56th Conference on Simulation and Modelling (SIMS 56) : October, 7-9, 2015, Linköping University, Sweden - Buffoni, Lena; Pop, Adrian; Thiele, Bernhard (Linköping Electronic Conference Proceedings, Proceedings of the 56th Conference on Simulation and Modelling (SIMS 56), October, 7-9, 2015, Linköping University, Sweden, 2015)
Welcome The 56th Conference on Simulation and Modelling will be held in Linköping, Sweden. Linköping is one of Sweden’s fastest growing cities. The population is constantly increasing and will soon surpass 150 000 inhabitants. It is currently Sweden’s fifth largest city and a part of the expansive region Twin Cities of Sweden. Linköping has long been characterized by world-class high technology in the fields of aviation, IT and the environment. There is a strong force of innovation especially in Mjärdevi Science Park—one of Europe’s leading technology parks, and at the highly ranked university, which stands for excellence and entrepreneurship. SIMS is the Scandinavian Simulation Society with members from the five Nordic countries Denmark, Finland, Norway, Sweden and Iceland. The SIMS history goes back to 1959. The goal of SIMS is to further the science and practice of modeling and simulation in all application areas and be a Scandinavian forum for information interchange among modeling and simulation professionals and non-professionals in Denmark, Finland, Norway and Sweden as well as a channel for information exchange between the Scandinavian modeling and simulation community and the international modeling and simulation communities. The ambition of the SIMS is to bring the field of modeling and simulation technology to a variety of application fields from energy extraction to building and automotive industries, resulting in more sustainable and ecological systems and reducing energy consumption and waste production. The scientific program includes technical sessions with submitted and invited papers and will cover broad aspects of simulation, modeling and optimization. The focus of the conference is split evenly between papers on simulation and optimization in a variety of applied contexts spanning domains such as oil extraction, automotive and building industries and more methodological papers on tools and technologies for simulation and modeling. This year we wanted to emphasize the importance of reducing ...